Morbidity burden of respiratory diseases attributable to ambient temperature: a case study in a subtropical city in China - Yiju Zhao; Zhao Huang; Shengyong Wang; Jianxiong Hu; Jianpeng Xiao; Xing Li; Tao Liu; Weilin Zeng; Lingchuan Guo; Qingfeng Du; Wenjun Ma (BMC, 2019)
Abstract Background There are significant associations between ambient temperature and respiratory disease mortality. However, few studies have assessed the morbidity burdens of various respiratory diseases that are attributable to different temperature ranges in subtropical regions. Methods Daily outpatient visits, weather variables, and air pollution data were collected from January 2013 to August 2017 in a hospital in Dongguan city. A standard time series quasi-Poisson regression with a distributed lag non-linear model (DLNM) was applied to estimate the associations between daily mean temperature and morbidity for total respiratory diseases, bronchiectasis, chronic obstructive pulmonary disease (COPD), and asthma. Attributable fractions were then calculated to quantify disease burden relative to different temperature components. Finally, we conducted stratified analysis by age group. Results Both low and high temperatures were associated with an increased risk of morbidity secondary to respiratory diseases. Compared with the optimum temperature, the accumulated relative risk (RR) during the seven lag days was 1.13 with a 95% confidence interval (CI) of 1.01-1.26 for extreme heat and 1.02 (95% CI: 0.99-1.05) for extreme cold. Heat-related respiratory morbidity risk was higher than cold-related risk for the total population, but an opposite result was observed for the elderly. About 8.4% (95% CI: 2.8-13.3%) of respiratory morbidity was attributable to non-optimal temperatures, and moderate heat was responsible for most of the excess respiratory morbidity (7.5, 95% CI: 2.4-12.2%). Conclusions We found that exposure to non-optimal temperatures increased the risk of respiratory morbidity in subtropical region, and moderate heat contributed to most of the temperature-related respiratory morbidities. This indicates a need for further examination of moderate, rather than extreme, heat in subtropical region.